2020
DOI: 10.1177/0193945919897547
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Associated with Physical Activity in Latino Immigrants

Abstract: Latinos are at increased risk for developing chronic conditions. Regular physical activity (PA) assists in protecting adults from developing type 2 diabetes, excess weight, and heart disease, making PA important for health promotion. This cross-sectional, descriptive investigation was conducted with adults 18 years of age and older in a predominately Latino community. Perceptions of factors which influenced PA were examined. Descriptive statistics and multiple regression analysis were performed. Immigrant Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Self‐efficacy, particularly when working with individuals at risk for diabetes, needs to be fostered as it may be one of the most important ways for individuals to feel confident in their ability to promote their own health (Amirehsani et al, 2019; Mikell et al, 2020). Latino men have reported that the energy they expend while working is adequate for maintaining health (Valdez et al, 2019); however, occupational activities do not provide the same cardiovascular benefits as leisure time physical activity (Holtermann et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Self‐efficacy, particularly when working with individuals at risk for diabetes, needs to be fostered as it may be one of the most important ways for individuals to feel confident in their ability to promote their own health (Amirehsani et al, 2019; Mikell et al, 2020). Latino men have reported that the energy they expend while working is adequate for maintaining health (Valdez et al, 2019); however, occupational activities do not provide the same cardiovascular benefits as leisure time physical activity (Holtermann et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, since not all these interventions are universally transferable, individuals with different traditions, such as those in specific ethnic groups, religious communities, immigrant clusters, and indigenous peoples often present lower levels of PA ( 74 76 ). Even when resources are available and the built environment is conducive to PA, the absence of cultural care can limit changes in this behavior ( 77 , 78 ). Accordingly, an increasing number of studies report that initiatives aiming at raising PA levels should take cultural backgrounds into consideration ( 64 , 76 , 79 ).…”
Section: Macro-environmental Dimensions Of Physical Activitymentioning
confidence: 99%
“…When I embarked on my fellowship, one of my goals was that I would develop my skills as a writer and publish the findings from my dissertation research. 9,10 The fellowship allowed time for reflection, which provided the impetus I needed to write manuscripts for submission to peerreviewed journals (it also provided a safe space to weather manuscript rejection). 6 When I received immediate "desk rejections" by editors, as well as rejections by reviewers who critiqued my work with enthusiasm and then rejected it, I viewed these as new opportunities to find the proper journal fit.…”
Section: Commitment To a Postdoctoral Positionmentioning
confidence: 99%